University Physics I Classical Mechanics - Gea-Banacloche, Julio; Open Textbook Library (Open Textbook Library, 2019)
This is a "minimalist" textbook for a first semester of university, calculus-based physics, covering classical mechanics (including one chapter on mechanical waves, but excluding fluids), plus a brief introduction to thermodynamics. The presentation owes much to Mazur's The Principles and Practice of Physics: conservation laws, momentum and energy, are introduced before forces, and one-dimensional setups are thoroughly explored before two-dimensional systems are considered. It contains both problems and worked-out examples.
1 Reference frames, displacement, and velocity -- 2 Acceleration -- 3 Momentum and Inertia -- 4 Kinetic Energy -- 5 Interactions and energy -- 6 Interactions, part 2: Forces -- 7 Impulse, Work and Power -- 8 Motion in two dimensions -- 9 Rotational dynamics -- 10 Gravity -- 11 Simple harmonic motion -- 12 Waves in one dimension -- 13 Thermodynamics
In English.
Description based on online resource
Keywords: Physics -- Textbooks